COMPARATIVE-STUDY OF OXIDATION OF CO3TI, COTI AND COTI2 BY X-RAY PHOTOELECTRON-SPECTROSCOPY - Garrett, S; Egdell, R (1992)
The interaction of Co3Ti, CoTi and CoTi2 with O 2 at room temperature has been studied by X-ray photoelectron spectroscopy (XPS). For all three materials, oxygen exposure in the regime up to 15000 L (1 L = 133.322 Pa s) leads to formation of a Ti oxide overlayer without oxidation of the Co component of the alloy. The rate of oxidation correlates with the density of states at the Fermi energy and follows the sequence Co 3Ti> CoTi> CoTi2.